2016
DOI: 10.1108/cb-03-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

A study on collection development and its organizational pattern of university libraries in Uttar Pradesh (India)

Abstract: Purpose – The purpose of the study is to know the collection development and its organizational pattern of university libraries in India. Design/methodology/approach – For the purpose of the study, three sets of questionnaire were prepared by the researcher and furnished to librarians and acquisition librarians (collection development in charge) of these referred libraries. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The study also assessed the impact of information and communication technology (ICT) on collection building at public libraries. The study by Khan (2010, 2016) has described collection development and its organizational pattern of university libraries in Uttar Pradesh, India. The survey revealed that the old centralized universities are better placed in terms of all the parameters of collection development and further revealed that the centralized universities established recently are lagging behind the old centralized universities in an organizational pattern of collection development.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The study also assessed the impact of information and communication technology (ICT) on collection building at public libraries. The study by Khan (2010, 2016) has described collection development and its organizational pattern of university libraries in Uttar Pradesh, India. The survey revealed that the old centralized universities are better placed in terms of all the parameters of collection development and further revealed that the centralized universities established recently are lagging behind the old centralized universities in an organizational pattern of collection development.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Moreover, Pradhan (2016) reveals that University library of Orissa are following suitable collection development practices which is evident from the impressive growth and overall development of University library despite of having new origin. Khan (2016) conducts a comparative analysis of collection development patterns among the four central University libraries of Uttar Pradesh (UP). The findings evidently reveal that newly centralized University libraries are lagging far behind the old centralized University libraries in collection development practices.…”
Section: Lasu Professionals Rolesmentioning
confidence: 99%
“…They have also evaluated the level of impact that ICT is having on the collection development process of public libraries. Khan (2010Khan ( , 2016 discussed the patterns of organization followed in university libraries of Uttar Pradesh, India. The study found that the earlier established centralized universities have better organizational pattern of collection development as compared to the centralized universities established recently.…”
Section: Review Of Related Literaturementioning
confidence: 99%